Exploración de materiales para sistemas de control pasivo de ruido implementado a diseño acústico bioclimático con potencial uso en la construcción sostenible (2019)
The concern about noise levels inside enclosure has increased in recent years. Therefore, it has dabbled in the search for a solution, the passive noise control has been a simple and effective answer for it. The passive noise control is a solution for de noise levels that can be found in the enclosure, because this is in charge of decreases them. The noise levels that affects an enclosure it’s due to ambient noise that is around it, this is influenced by several factors, such as: the industry, the traffic and the other factors that are there in the environment. The passive noise control can be implemented on any of the noise points (source – way – receptor), which is particularly, useful according to what people needs, to decrease noise levels inside enclosure the most effective is to monitor the facades, this control must be done with materials with acoustic characteristics, such as, sound reduction index and absorption coefficient. The most frequently implemented materials for the noise control are wool, drywall and concrete, although efficient in terms of absorption, these materials do not have optimal characteristics to be part of the bioclimatic design. The bioclimatic consider sustainable materials as optimal for any type of construction, because they do not pollute and help improve oxygen. The objective of this investigation is to find the acoustic characteristics on a different type of material than conventional, which are not contaminant, and besides, accomplish with adequate acoustic characteristics to replace the conventional ones. The methodology to be developed will start in the search and characterization material. By means of the P-U lead, for later get a cost-benefit analysis of the material implementation. With the obtained data through measurements and calculations it is evident that the green walls are a potential tool for the passive control of noise with bioclimatic design, since they meet the bioclimatic characteristics of comfort and has attenuations throughout the frequency range if it is a composite partition that is accompanied by concrete, or in high frequencies if the only installation is a vertical garden.